2017
DOI: 10.7762/cnr.2017.6.1.47
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary Antioxidant Capacity and Its Association with Preeclampsia

Abstract: Preeclampsia (PE) is one of the major disorders in pregnancy leading to many adverse maternal outcomes. Although the etiology of PE is not fully understood, resent studies suggest that an imbalance between free radicals production and the antioxidant defense system might have key role. Our aim of the current study was to evaluate the association between dietary total antioxidant capacity (TAC), serum TAC and risk of PE in women with preeclampsia and normal pregnancy. This case-control study conducted on 55 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The current results indicated that TAC in kids from birth to 4 weeks of age tended to increase, but not significantly ( Figure 1). It is postulated that TAC serum concentration in kids is associated with the maternal health and nutrition [7]. Serum TBARS concentrations increased on the 2 nd week and decreased significantly on the 4 th week of age ( Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…The current results indicated that TAC in kids from birth to 4 weeks of age tended to increase, but not significantly ( Figure 1). It is postulated that TAC serum concentration in kids is associated with the maternal health and nutrition [7]. Serum TBARS concentrations increased on the 2 nd week and decreased significantly on the 4 th week of age ( Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…Countering reactive oxygen species released during pre-eclampsia are solely dependent on total endogenous antioxidants present in the system. Mahdiyeh et al [28] observed that serum TAC is positively associated with the risk of preeclampsia but no association was found between intake of antioxidant indices and pre-eclampsia risk. The TAC of pregnant women is reduced by high lipid peroxidation, abnormal placentation, oxidative stress, alcoholism, smoking and exposure to radiation and toxic elements.…”
Section: Resultsmentioning
confidence: 99%
“…A study (28) showed PE women had significantly lower intakes of milk, meat or beans and higher consumption of grains and fruit, vegetables compared to the recommended minimum number for pregnant women. However, in the case control study in Isfahan, PE women had significantly lower intakes of grains and vegetables compared to the normal pregnancy (29). Another study reported that women who had high intakes of vegetables had lower PE risk (30).…”
Section: Discussionmentioning
confidence: 96%